EFEKTIVITAS PENEGAKAN HUKUM TERHADAP BANDAR NARKOTIKA YANG BERSTATUS WARGA BINAAN DI LAPAS KELAS IIA TARAKAN PROVINSI KALIMANTAN UTARA - Rifal Rifal (JURNAL AKTA YUDISIA, 2026)
This research aims to analyze the effectiveness of law enforcement against drug kingpins who hold the status of inmates at Class IIA Tarakan Correctional Facility, from the North Kalimantan Province National Narcotics Agency. Based on the background, this study raises two main issues: the enforcement of law against inmates with drug kingpin status in preventing recidivism and the factors that contribute to their tendency to re-offend after serving their sentences. This research employs a normative legal research type, using a statutory approach and a conceptual approach. Based on the findings, the effectiveness of law enforcement in preventing drug kingpin recidivism still faces numerous challenges, particularly in terms of supervision, rehabilitation, and dismantling criminal networks. If the correctional system continues to have loopholes, even the harshest punishments will not be effective in stopping their crimes. Therefore, a more comprehensive legal approach, including rehabilitation and correctional system reforms, is crucial in preventing repeat offenses. Furthermore, the recidivism of drug kingpins is triggered by financial dependence, a criminal mindset, and addiction. Pressure from criminal networks, lack of social support, and an unhealthy environment further exacerbate the situation. A weak correctional system, corruption within prisons, and inadequate reintegration programs also contribute to the problem. Additionally, difficulty in finding employment and poverty drive them back into the drug trade. Preventive efforts require effective rehabilitation, economic empowerment, and stricter law enforcement.